Impact of Selected Personality Traits on Accountants’ Attitudes Toward Accounts Manipulation: Evidence From Slovenia - Horvat, Robert (Naše gospodarstvo/Our economy, 2018)
In the study, three selected personality traits were tested for their impact on Slovenian accountants’ attitudes toward accounts manipulation behavior. The main objective was to investigate if personality plays a role in how Slovenian accountants think and feel about this ethically problematic business practice. Responses from 310 chief accounting officers of Slovenian medium- and large- size companies were gathered via electronic survey, and correlational and regression analyses were performed to investigate relationships between selected personality traits and participants responses to the scenario, thus depicting accounts manipulation behavior in violation of generally accepted accounting principles. Only two of the observed personality traits (Machiavellianism and agreeableness) were found to be statistically significantly related to accountants’ attitudes, while the third one (locus of control) shows no such relationship. For both, Machiavellianism and agreeableness, the direction of the relationship with accountants’ attitudes is the same. The higher the levels of accountants’ Machiavellianism and agreeableness, the more positive their attitude toward observed accounts manipulation behavior.